Is Inhaler Technique Associated with Quality of Life in Patients with Chronic Obstructive Pulmonary Disease? - Shahideh Amini, PharmD; Arezou Ghasemi, PharmD; Mohammad Solduzian, PharmD; Besharat Rahimi, MD; Kazem Heidari, MD; Molouk Hadjibabaie, PharmD; Mona Kargar, PharmD (Elsevier, 2020)
ABSTRACT: Background: Inhalers are the mainstay of treatment for patients suffering from chronic obstructive pulmonary disease. However, incorrect inhaler technique is a considerable challenge. Objective: We aimed to evaluate inhaler technique and its association with quality of life in a sample of patients with chronic obstructive pulmonary disease. Methods: This cross-sectional study included patients with confirmed chronic obstructive pulmonary disease who were prescribed at least 1 inhaler medication on a regular basis. Patients were recruited from the outpatient pulmonary clinic of a hospital in Tehran. Inhaler technique was assessed according to a validated checklist. Patients' quality of life was evaluated using Chronic Obstructive Pulmonary Disease Assessment Test. Results: One hundred seventy-five patients with mean (SD) age of 59.0 (10.1) years were included. Patients' devices were 192 (62.3%) pressurized metered-dose inhalers (including pressurized metered-dose inhalers plus spacer) and 116 (37.7%) dry powder inhalers. Unfortunately, only 2.86% of patients used their inhalers completely correct. The highest rate of errors was committed by patients who used metered-dose inhalers plus spacer. Patients with a higher educational degree had significantly lower rate of errors on average (P = 0.001). The most frequent errors made by patients using pressurized metered-dose inhalers or Turbuhaler was priming the inhaler before the first administration in 90.6% and 78.3% of patients, respectively. Chronic Obstructive Pulmonary Disease Assessment Test scores in patients using different inhaler devices were not significantly different. However, in patients with lower quality of life, significantly more patients had poor inhaler technique (P = 0.0001). Conclusions: There is still considerable need for interventions to optimize inhaler technique. We also noted that appropriate inhaler technique is associated with better quality of life. (Curr Ther Res Clin Exp. 2020; 81:XXX-XXX)